Dābiq et la frontière du Dār al-Islām - Eva Collet (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: This article aims to show how the Umayyad and Abbasid Muslim powers appropriated this new frontier area, shedding light on the representations of Dābiq in Arab-Muslim historiography. At the time of the first Umayyads (40-95 H./661-715), this area was transformed by the arrival of the first garrisons to monitor the border and of Arab tribes seeking to control new territories and resources. Between 96 H./715 and 132 H./750 emerged in the Arab-Muslim literature mythologised figures Umayyad related to Dābiq. Under the first Abbasids (130-210 H./750-830), the sources consistently convey the fear of a Byzantine reconquest of Dābiq and its surroundings, through the creation of an eschatological literature. This area is then relegated to the background as the military front in Cilicia is gradually consolidating. The eschatological prophetic tradition on Dābiq and al-A'māq can hypothetically be traced back and date. These hypotheses will be presented at the end of the article.